Proceedings of Second International Conference on Electrical Systems, Technology and Information 2015 (ICESTI 2015) - Pasila, Felix; Tanoto, Yusak; Lim, Resmana; Santoso, Murtiyanto; Pah, Nemuel Daniel; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book includes the original, peer-reviewed research papers from the 2nd International Conference on Electrical Systems, Technology and Information (ICESTI 2015), held in September 2015 at Patra Jasa Resort & Villas Bali, Indonesia. Topics covered include: Mechatronics and Robotics, Circuits and Systems, Power and Energy Systems, Control and Industrial Automation, and Information Theory.    It explores emerging technologies and their application in a broad range of engineering disciplines, including communication technologies and smart grids. It examines hybrid intelligent and knowledge-based control, embedded systems, and machine learning. It also presents emerging research and recent application in green energy system and storage. It discusses the role of electrical engineering in biomedical, industrial and mechanical systems, as well as multimedia systems and applications, computer vision and image and signal processing. The primary objectiveof this series is to provide references for dissemination and discussion of the above topics. This volume is unique in that it includes work related to hybrid intelligent control and its applications. Engineers and researchers as well as teachers from academia and professionals in industry and government will gain valuable insights into interdisciplinary solutions in the field of emerging electrical technologies and its applications.
Computational Intelligence based Regulation of the DC bus in the On-Grid Photovoltaic System -- Virtual Prototyping of a Compliant Spindle for Robotic Deburring -- A Concept of Multi Rough Sets Defined on Multi-Contextual Information Systems -- Coordinates Modelling of the Discrete Hexapod Manipulator via Artificial Intelligence -- An Object Recognition in Video Image Using Computer Vision -- Comparative Study on Mammogram Image Enhancement Methods According to the Determinant of Radiography Image Quality -- Clustering and Principal Feature Selection Impact for Internet Traffic Classification Using K-NN -- Altitude Lock Capability Benchmarking: Type 2 Fuzzy, Type 1 Fuzzy, and Fuzzy-PID with Extreme Altitude Change as a Disturbance -- Indonesian Dynamic Sign Language Recognition at Complex Background with 2D Convolutional Neural Networks -- Image-based Distance Change Identification by Segment Correlation -- Situation Awareness Assessment Mechanism for a Telepresence Robot.
Keywords: Control engineering; Robotics; Automation; Electric power production; Electrical engineering; Computer networks .; Control, Robotics, Automation; Electrical Power Engineering; Mechanical Power Engineering; Electrical and Electronic Engineering; Computer Communication Networks